Legal Status of Migrants Stranded at International Borders - Hamdi , Abdulrahman; Farhad , Reagr; Ghani , Hemn (Journal of Legal Sciences, 2025)
The phenomenon of migrants stranded at international borders has recently attracted attention, highlighting their plight and human tragedy. This tragedy stems from the lack of a comprehensive legal framework applicable to this category of migrants, a framework designed to prevent the exploitation of their suffering and precarious legal status under flimsy pretexts and justifications that should never have been used to justify such actions. Human beings are being exploited under the pretext that they are illegal and unnatural migrants in the game of politics and in operations to provide security and guard international borders. Therefore, we have chosen to address in this research the legal status of this category of migrants, and to present the legal dimensions, or rather the loopholes, in their legal situation, which prevent them from resorting to the necessary legal means and expose them to Their situation is so degrading to their humanity and dignity that it is unacceptable to the human conscience and abhors the principles of justice and fairness. As a consequence of this precarious legal status, these migrants have been sacrificed to secure national borders. Even the countries forced to deal with this group of migrants perceived it as a failure to secure their borders, rather than an inability to provide the necessary legal protection.